After Action Reviews of COVID‐19 response: Case study of a large tertiary care hospital in Italy. (6th June 2021) - Sorbello, Sebastiano; Bossi, Eleonora; Zandalasini, Camilla; Carioli, Greta; Signorelli, Carlo; Ciceri, Fabio; Ambrosio, Alberto; Zangrillo, Alberto; Odone, Anna
Abstract: Background: After‐Action Reviews (AARs) are management tools used to evaluate the response to public health emergencies at the national and subnational level. Aim of this study is to apply available AAR models to assess and critically appraise COVID‐19 response of San Raffaele Scientific Institute, a large university hospital in Milan, Italy. Methods: We designed an AAR based on the key‐informant interview format, following the methodology proposed by the 2019 World Health Organization Guidance for AAR. After systematic assessment of the hospital reorganization, we conducted 36 semi‐structured interviews to professionals with executive, clinical, technical and administrative roles. We designed an ad‐hoc questionnaire exploring four areas: (i) staff management; (ii) logistics and supplies; (iii) COVID‐19 diagnosis and clinical management; (iv) communication. Results: Overall, the hospital response was evaluated as effective and sufficiently prompt. Participants stressed the relevance of: (i) strong governance and coordination; (ii) readiness and availability of healthcare personnel; (iii) definition of a model of care based on a multidisciplinary approach. Challenges were reported for communication management and staff training. Conclusions: This study is one of the first applications of the AAR to the COVID‐19 response in hospital settings, which can be successfully adapted or scaled up to other settings in order to implement preparedness strategies for future public health emergencies.